The Biochemistry of Sabella spallanzanii (Annelida: Polychaeta): A Potential Resource for the Fish Feed Industry. Issue 3 (9th June 2013) - Stabili, L.; Sicuro, B.; Daprà, F.; Gai, F.; Abete, C.; Dibenedetto, A.; Pastore, C.; Schirosi, R.; Giangrande, A.
ABSTRACT To prevent over‐exploitation of global fish stocks by the aquaculture industry, interest is growing in the identification of nontraditional species with potential value as fish feed. In this study, we investigated the biochemical composition of the polychaete Sabella spallanzanii. Its elemental composition, gross protein and proximate composition, amino acid composition, total lipid and fatty acid content, glycosaminoglycan (GAG) content and the extent of polychlorinated biphenyl contamination were determined over an annual cycle. Sabella spallanzanii showed particularly high gross protein (54.8 ± 5.8%) and gross energy (4.89 ± 0.5 kcal/g) content. All samples had high concentrations of Na, K, Ca, and Cl. Saturated fatty acids were higher than monounsaturated and polyunsaturated ones. A low ω‐6/ω‐3 ratio (1.7) was recorded. Our results suggest that S. spallanzanii can be used as a dietary supplement for farmed fish. The high concentrations of certain amino acids that improve potential palatability for many farmed fish species suggest that S. spallanzanii extracts can be used in artificial fish diets as an attractant. A further original aspect highlighted by this study is the high concentration of GAGs, which are useful in pet nutrition and also in the nourishment of farmed fish with a partially cartilaginous skeleton.